A nano-colloidal hydrogel and preparation method thereof
Through nanoengineering strategies, natural linear polymers are prepared into nanoparticles, which solves the problems of structural instability and reduced mechanical properties caused by swelling of hydrogels in aqueous media, and realizes the preparation of non-swelling nanocolloid hydrogels. It has long-term stable mechanical properties and a wide range of application scenarios.
Patent Information
- Application Number
- CN202410252920.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-03-06
AI Technical Summary
The swelling of existing hydrogels in aqueous media leads to structural instability, reduced mechanical properties, and may cause physiological and pathological reactions. At the same time, the formation of nanocolloid hydrogels requires high concentrations of nanoparticles to lead to opacity, limiting its application.
Natural linear polymers are prepared into nanoparticles through nanoengineering strategies, and non-swelling nanocolloidal hydrogels are prepared using photoinitiators and crosslinking agents, which solves the problems of low solubility and high viscosity, and is not subject to temperature and The degree of crosslinking affects the swelling stability.
The solubility and viscosity reduction of natural polymer hydrogels have been achieved, and an inswellable nanocolloidal hydrogel is prepared, with long-term stable mechanical properties and a wide range of application scenarios, and significantly improves the anti-degradation ability and low friction properties.
Smart Images

Figure CN118126351B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer hydrogels, and in particular relates to a nano-colloidal hydrogel and a preparation method thereof. Background Art
[0002] Hydrogel is a new type of functional polymer material, which has been widely used in biomedical fields such as wound dressings, drug release carriers, tissue filling materials, tissue engineering scaffolds and cosmetic materials. Natural polymer hydrogels have attracted widespread attention from researchers due to their good biocompatibility and degradability, simple and easy to obtain materials, etc. Nanocolloidal hydrogel is a new type of soft material. Nanocolloidal hydrogels are prepared by physical or chemical interactions between nanocolloids using nanocolloids of different shapes, sizes and compositions as building blocks. Compared with traditional hydrogels prepared from linear polymers, nanocolloidal hydrogels have the advantages of nonlinear mechanical properties, multi-scale structures and enhanced transport properties.
[0003] Due to the mismatch of osmotic pressure, hydrogels inevitably swell in aqueous media. High swelling degree will damage the structural stability of hydrogels, reduce the mechanical properties of hydrogels and significantly change the permeability of hydrogels. At the same time, the volume increase caused by swelling will cause compression of tissues and nerves at the hydrogel filling site, leading to some adverse physiological and pathological reactions. In order to meet these challenges, people have developed a variety of strategies to prepare non-swelling hydrogels, including adjusting the cross-linking density, using hydrophobic polymer chains, or adding thermal responsive units with low critical temperatures to the hydrogel network. However, the hydrophilic-hydrophobic balance in the hydrogel network is usually adjusted by changing the component concentration or raw material composition to achieve appropriate non-swelling properties. In addition, the anti-swelling properties of these hydrogels are usually temperature-dependent, which limits their scope of use. And driven by electrostatic interactions, the formation of nanocolloidal hydrogels requires relatively high concentrations of nanoparticles. This situation often results in opaque hydrogels, limiting their further application in three-dimensional cell culture and other fields requiring transparent hydrogels. In addition, nanocolloidal hydrogels formed by directly mixing mutually attractive nanocolloidal building blocks often experience uncontrollable aggregation and phase separation, which affects their structural uniformity and mechanical properties. To this end, we propose a nanocolloidal hydrogel and a preparation method thereof. Summary of the invention
[0004] The object of the present invention is to provide a nano-colloidal hydrogel and a preparation method thereof, aiming to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing a nano-colloidal hydrogel comprises the following steps:
[0007] Step S1, preparation of HAMA NPs: after HA is fully dissolved in deionized water, MA is added dropwise to the solution in a certain proportion under ice-water bath conditions to fully react, and a certain proportion of carbon-carbon double bonds are grafted on the surface of sodium hyaluronate to obtain a HAMA solution; the HAMA solution after the reaction is dialyzed and freeze-dried, and then redissolved in deionized water, and the carboxyl groups on the polymer chains are activated with EDC, and acetone is added to the solution to desolvate the polymer, and then a cross-linking agent is added to cross-link the polymer chains to obtain a nanoparticle solution with a certain size, and the solution is dialyzed again and concentrated to obtain a HAMA NPs solution;
[0008] Step S2, preparation of nano-colloidal hydrogel: the HAMA NPs solution obtained in step S1 is redispersed in a PBS solution containing 0.05 w / v% photoinitiator to prepare hydrogel precursor solutions with different concentrations; a certain volume of the precursor solution is then loaded into a polytetrafluoroethylene mold, and then irradiated with an ultraviolet light source to prepare a nano-colloidal hydrogel.
[0009] Furthermore, in step S1, the temperature of the ice water bath is controlled at 0-4°C.
[0010] Furthermore, in step S1, the cross-linking agent is ADH, spermidine or spermine.
[0011] Furthermore, in step S2, the photoinitiator is Irgacure 2959 or 2,4,6-trimethylbenzophenone or lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP).
[0012] Furthermore, in step S2, the wavelength of the ultraviolet light source is 365nm; the light intensity of the ultraviolet light source is greater than 10mW / cm 2 .
[0013] A nano-colloidal hydrogel prepared by the preparation method described above.
[0014] Compared with the prior art, the present invention has the following beneficial effects:
[0015] 1. The present invention adopts a nano-engineering strategy to prepare natural linear polymers into nanoparticles, thereby improving the solubility of natural polymers, broadening the use concentration of natural polymers, effectively reducing the viscosity of natural polymers, and solving the problems of low solubility and high viscosity of natural linear polymers during application.
[0016] 2. The present invention realizes the preparation of non-swelling nano-colloidal hydrogel.
[0017] 3. The swelling of the nano-colloidal hydrogel prepared by the present invention is not affected by temperature and cross-linking degree, has a wide range of application scenarios, and has long-term stable mechanical properties before and after swelling.
[0018] 4. The present invention significantly improves the in vivo and in vitro anti-degradation ability of natural polymer-based hydrogels, achieving long-term non-degradation in vivo and in vitro.
[0019] 5. The present invention realizes the preparation of nano-colloidal hydrogel with low friction properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic diagram of the synthetic structure of the nano-colloidal hydrogel in the present invention.
[0021] Figure 2 This is a transmission electron micrograph of 28%-HAMA NPs of the present invention.
[0022] Figure 3 This is the size distribution diagram of 28%-HAMA NPs in the present invention.
[0023] Figure 4 This is a macroscopic photograph of the nanocolloid hydrogel prepared with 25 mg / mL 28%-HAMA NPs in the present invention.
[0024] Figure 5 This is a cryo-scanning electron micrograph of the nanocolloidal hydrogel prepared from 25 mg / mL 28%-HAMA NPs in the present invention.
[0025] Figure 6 The degradation of the nanocolloid hydrogel prepared with 25 mg / mL 28%-HAMA NPs in the present invention within 90 days.
[0026] Figure 7 The cell biocompatibility of the nanocolloid hydrogel with different substitution degrees of the present invention.
[0027] Figure 8 The figure shows the degradation of the nano-colloid hydrogel prepared by 25 mg / mL 28%-HAMA NPs in the present invention in mice.
[0028] Fig. 9 This is a test of the friction coefficient of 25 mg / mL nanocolloid hydrogels with different degrees of substitution in the present invention.
[0029] Fig.10 It is the modulus of the nanocolloid hydrogel prepared with 25 mg / mL 22%-HAMA NPs in the present invention.
[0030] Fig.11This is the volume swelling of the nanocolloid hydrogel prepared with 25 mg / mL 22%-HAMA NPs at 25°C in the present invention.
[0031] Fig.12 This is the mass swelling of the nanocolloid hydrogel prepared with 25 mg / mL 22%-HAMA NPs at 25°C in the present invention. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0033] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0034] like Figure 1 As shown, a method for preparing a nano-colloidal hydrogel provided by an embodiment of the present invention comprises the following steps:
[0035] Step S1, preparation of methacryloylated hyaluronic acid nanoparticles (HAMA NPs): after sodium hyaluronate (HA) is fully dissolved in deionized water, methacrylic anhydride (MA) is added to the solution in a certain proportion under 0-4°C ice-water bath conditions, and fully reacted, a certain proportion of carbon-carbon double bonds are grafted on the surface of sodium hyaluronate to obtain a methacryloylated hyaluronic acid (HAMA) solution. The HAMA solution after the reaction is dialyzed and freeze-dried, and then redissolved in deionized water, and a large number of carboxyl groups on the polymer chain are activated with 1-ethyl-(3-dimethylaminopropyl) carbodiimide (EDC), and acetone is added to the solution to desolvate the polymer, and then a cross-linking agent adipic acid dihydrazide (ADH) is added to cross-link the polymer chain and obtain a nanoparticle solution of a certain size, and the solution is dialyzed again and concentrated to obtain a methacryloylated hyaluronic acid nanoparticle (HAMA NPs) solution.
[0036] Step S2, preparation of nanocolloidal hydrogel: The HAMA NPs solution obtained in step S1 was redispersed in a phosphate buffered saline (PBS) solution containing 0.05 w / v% photoinitiator Irgacure 2959 to prepare hydrogel precursor solutions with different concentrations. A certain volume of the precursor solution was then placed in a polytetrafluoroethylene mold, and then irradiated with a 365 nm ultraviolet light source to prepare a nanocolloidal hydrogel.
[0037] In the embodiment of the present invention, gelatin nanoparticles or chitosan nanoparticles can also be prepared, and the above HAMANPs and gelatin nanoparticles or chitosan nanoparticles are blended to prepare a composite nanocolloidal hydrogel.
[0038] The preparation method of gelatin nanoparticles is as follows: using the amino group of gelatin and glutaraldehyde for cross-linking, and using acetone for desolvation to prepare gelatin nanoparticles;
[0039] The preparation method of chitosan nanoparticles comprises the following steps: cross-linking the amino groups of chitosan chains with glutaraldehyde and desolvating with acetone to prepare the chitosan nanoparticles.
[0040] Embodiment 1: A method for preparing a nano-colloidal hydrogel provided by an embodiment of the present invention comprises the following steps:
[0041] S1: Add 1g sodium hyaluronate powder (HA, Mw = 150-250KDa) to 100mL deionized water and fully dissolve it. Transfer the solution to an ice water bath at 0-4°C, add 4mL of methacrylic anhydride solution (MA) to the solution, adjust the pH of the solution to 8-9 with 5M sodium hydroxide solution, and react at 0-4°C for 24h to obtain a methacrylylated hyaluronic acid (HAMA) solution. The obtained HAMA solution is reverse precipitated in ethanol, centrifuged, the supernatant is discarded, and the precipitate is redissolved in deionized water. After dialysis for 72h, it is freeze-dried to obtain 0.8g HAMA powder. Weigh the freeze-dried powder and dissolve it in a deuterated water solvent to a concentration of 5mg / mL. The double bonds grafted on the HA surface are quantified by a nuclear magnetic resonance spectrometer. The proportion of double bonds grafted on the HA surface is 28%, expressed as 28%-HAMA.
[0042] S2: 80 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) was dissolved in 2 mL of deionized water to prepare an EDC solution; 40 mg of adipic acid dihydrazide (ADH) was dissolved in 2 mL of deionized water to prepare an ADH solution.
[0043] S3: Weigh 0.2g of 28%-HAMA powder and dissolve it in 80mL deionized water. After fully dissolved, add 132mL acetone and stir it at room temperature for 30min. Add EDC solution and ADH solution dropwise to the 28%-HAMA solution. After fully stirring for 30min, add 130mL acetone to the solution again. After cross-linking for 3-5h, obtain 28%-HAMA nanoparticles (28%-HAMANPs) solution. The obtained 28%-HAMA NPs solution is fully dialyzed in water and concentrated by rotary evaporation. Take 200μL of concentrated 28%-HAMA NPs solution, dry it in a vacuum oven at 60℃, determine the concentration of the concentrate, dilute the concentrate with PBS solutions of different concentrations, and obtain 30mg / mL 28%-HAMA NPs PBS solution.
[0044] The morphology of 28%-HAMA NPs was characterized by transmission electron microscopy (TEM). Figure 2 As shown, the diameter of the nanoparticles was determined to be 25 ± 5 nm by measuring the nanoparticles obtained by transmission electron microscopy. Figure 3 shown.
[0045] S4: Prepare a 0.3 w / v% aqueous solution of photoinitiator Irgacure 2959. Blend 500 μL of 30 mg / mL 28%-HAMA NPs solution with 100 μL of 0.3 w / v% photoinitiator solution to prepare a hydrogel precursor solution. Spread the precursor solution on a 2 cm diameter polytetrafluoroethylene mold and irradiate with a 365 nm UV light source at 10 mW / cm 2 The precursor solution was photo-crosslinked to prepare nano-colloidal hydrogel by irradiation with light intensity of 120s.
[0046] In the present embodiment, the nano-colloidal hydrogel obtained in Example 1 was photographed with a camera. Figure 4 , the macroscopic morphology of the nanocolloidal hydrogel can be seen.
[0047] S5: The prepared nanocolloid hydrogel was cut into strips of 1 cm in length and 2 mm in width, frozen and fixed by a high-pressure freezer, and transferred to a cryo-scanning electron microscope by vacuum freezing. The nanocolloid hydrogel was tested to obtain the internal structure of the nanocolloid hydrogel, such as Figure 5 shown.
[0048] S6: The prepared nanocolloidal hydrogel was carefully transferred to the rheometer platform, and a strain test experiment was performed at 25°C, 0.1% to 100% strain amplitude, and 0.1 Hz constant frequency.
[0049] The storage modulus G' and loss modulus G" of the nanocolloidal hydrogel were measured to be 7005.4Pa and 883.798Pa respectively.
[0050] S7: Monitoring the swelling behavior of nanocolloidal hydrogels.
[0051] Mass swelling: The prepared nanocolloid hydrogel was weighed and used as the initial mass W0 of the nanocolloid hydrogel. The nanocolloid hydrogel was then transferred to a polystyrene culture dish containing 5 mL of PBS solution to fully immerse the nanocolloid hydrogel. At regular intervals (24 h), the nanocolloid hydrogel sample was taken out of the culture dish, the PBS solution on the surface of the nanocolloid hydrogel was carefully removed with filter paper, and the sample was weighed again to obtain the mass W of the nanocolloid hydrogel at different times. t The swelling ratio (SR) is calculated by the following formula:
[0052] Volume swelling: A glass capillary with an inner diameter of 0.9-1.1 mm was treated with hydrophobicity, and then a cylindrical nanocolloidal hydrogel was prepared in the capillary. The nanocolloidal hydrogel sample was removed from the capillary and transferred to a polystyrene culture dish with a diameter of 3.5 cm. The initial diameter d0 of the cylindrical nanocolloidal hydrogel was measured using an optical microscope, and then the nanocolloidal hydrogel sample was placed in a PBS solution and immersed. After a certain period of time, the diameter d0 of the cylindrical nanocolloidal hydrogel was measured again using an optical microscope. t The swelling ratio (SR) is calculated by the following formula:
[0053] The mass swelling ratio of the nanocolloidal hydrogel was calculated to be 99.98±2.47%.
[0054] The volume swelling ratio of the nanocolloidal hydrogel was calculated to be 100.8±0.95%.
[0055] S8: After soaking the nanocolloidal hydrogels of different components in PBS solution for 7 days, 15 days, and 30 days, the nanocolloidal hydrogel samples were taken out from the solution, and the surface moisture was absorbed with filter paper. Then, the nanocolloidal hydrogel was transferred to the rheometer platform, and strain test experiments were carried out at 25°C, 0.1% to 100% strain amplitude, and 0.1 Hz constant frequency to determine the effect of swelling on the mechanical properties of the nanocolloidal hydrogel.
[0056] The storage modulus and loss modulus of the nanocolloidal hydrogel changed to 6265.77 Pa and 682.10 Pa, 5721.7 Pa and 554.85 Pa, and 5351.97 Pa and 765.83 Pa, respectively. By comparison, the mechanical properties of the nanocolloidal hydrogel were stable during the 30-day test, and no obvious decrease in modulus was observed.
[0057] S9: In vitro degradation: A glass capillary with an inner diameter of 0.9-1.1 mm was treated with hydrophobicity, and then cylindrical nanocolloidal hydrogels were prepared in the capillary. The nanocolloidal hydrogel samples were removed from the capillary and transferred to a polystyrene culture dish with a diameter of 3.5 cm and immersed in 5 mL of PBS solution containing 200-500 units / mL hyaluronidase, and the enzyme solution was replaced every 48 h.
[0058] During the 90 days of monitoring, no significant degradation was observed. Figure 6 shown.
[0059] S10: 30 mg / mL of 28%-HAMA NPs and 0.1% RGD-peptide were mixed to obtain a precursor solution of nanocolloid hydrogel, and then 3×10 4 L929 cells and 400μL precursor solution were mixed evenly, inoculated into 24-well plates, and nanocolloid hydrogels were prepared by UV polymerization to encapsulate L929 cells in nanocolloid hydrogels in three dimensions. An appropriate volume of complete culture medium was added to the well plate. Three days later, the culture medium was removed, 250μL Calcein-AM / PI reagent was added to each well, incubated at 37℃ for 20min, and the cell status was observed using a fluorescence microscope.
[0060] like Figure 7 As shown, the cell viability was good and no obvious cell death was observed, indicating that the nanocolloidal hydrogel had good cell biocompatibility.
[0061] S11: In vivo degradation: Mice were anesthetized with isoflurane (2-2.5%) and buprenorphine (0.5 mg kg -1 ) to relieve pain. The hair on the back of the mouse was removed with scissors and depilatory cream. A small 1 cm incision was made on the skin of the mouse's back perpendicular to the midline. The fascia was separated with scissors, and then 4 independent nanocolloid hydrogels (5 mm in diameter and 1.5 mm in thickness) were implanted subcutaneously, and the skin was sutured with 4-0 Vicryl sutures. The mice were monitored regularly, and the mice were sacrificed after 1 month, 2 months, 4 months, and 6 months, and the implanted nanocolloid hydrogels were removed from the back. The diameter of the nanocolloid hydrogel was measured, and no obvious degradation of the nanocolloid hydrogel in the mouse body was observed, such as Figure 8 shown.
[0062] S12: In vivo biocompatibility of nanocolloidal hydrogel The blood compatibility of nanocolloidal hydrogel was further verified by hemolysis experiment.
[0063] Using Triton X-100 as a positive control, the hemolysis rate was determined to be <1%. Secondly, by observing the histological changes of the nanocolloid hydrogel in the skin, heart, liver, spleen, lung, and kidney tissues after implantation, it can be seen that the nanocolloid hydrogel has good in vivo biocompatibility.
[0064] S13: Lubrication properties of nanocolloidal hydrogel: The nanocolloidal hydrogel was transferred to the rheometer platform and heated at 25 °C and 0.1 s -1 The torque test experiment was carried out under a constant shear rate and an axial force of 0.1N.
[0065] The friction coefficient of the nanocolloid hydrogel is calculated to be 0.002. Fig. 9 shown.
[0066] Embodiment 2: A method for preparing a nano-colloidal hydrogel provided by an embodiment of the present invention comprises the following steps:
[0067] S1: The difference from step S1 of Example 1 is that 2 mL of methacrylic anhydride solution (MA) is added dropwise to the solution, and the ratio of double bonds grafted on the surface of HA is 15%, expressed as 15%-HAMA. The rest is the same as step S1 of Example 1.
[0068] S2: Same as step S2 in Example 1.
[0069] S3: The difference from step S3 of Example 1 is that 28%-HAMA is replaced with 15%-HAMA to obtain a 30 mg / mL 15%-HAMA NPs PBS solution. The rest is the same as step S3 of Example 1.
[0070] The morphology of 15%-HAMA NPs was characterized by transmission electron microscopy (TEM), and the diameter of the nanoparticles was determined to be 28±5 nm by measuring the nanoparticles obtained by transmission electron microscopy.
[0071] S4: The difference from step S4 of Example 1 is that the 30 mg / mL 28%-HAMA NPs solution is replaced by a 30 mg / mL 15%-HAMA NPs solution. The rest is the same as step S4 of Example 1.
[0072] S5: Same as step S6 in Example 1.
[0073] The storage modulus G' and loss modulus G" of the hydrogel were measured to be 2041.8 Pa and 194.57 Pa, respectively.
[0074] S6: Same as step S7 in Example 1.
[0075] The mass swelling ratio of the nanocolloidal hydrogel was calculated to be 102.25±5.3%.
[0076] The volume swelling ratio of the nanocolloidal hydrogel was calculated to be 101.71±0.65%.
[0077] S7: Same as step S8 in Example 1.
[0078] The storage modulus and loss modulus of the nanocolloid hydrogel changed to 2425.3 Pa and 231.32 Pa, 1816.88 Pa and 121.72 Pa, and 1626.76 Pa and 148.15 Pa, respectively. By comparison, the mechanical properties of the nanocolloid hydrogel were stable during the 30-day test, and no obvious decrease in modulus was observed.
[0079] S8: Same as step S9 in embodiment 1.
[0080] During the 30 days of monitoring, the nanocolloidal hydrogel was gradually and completely degraded.
[0081] S9: The difference from step S10 in Example 1 is that the 30 mg / mL 28%-HAMA NPs solution is replaced with a 30 mg / mL 15%-HAMA NPs solution. The rest is the same as step S10 in Example 1.
[0082] like Figure 7 As shown, the cell viability was good and no obvious cell death was observed, indicating that the nanocolloidal hydrogel had good cell biocompatibility.
[0083] S10: Same as step S12 in embodiment 1.
[0084] Triton X-100 was used as a positive control, and the hemolysis rate was determined to be <1%.
[0085] S11: Same as step S13 in Example 1.
[0086] The friction coefficient of the nanocolloid hydrogel is calculated to be 0.0017. Fig. 9 shown.
[0087] Embodiment 3: A method for preparing a nano-colloidal hydrogel provided by an embodiment of the present invention comprises the following steps:
[0088] S1: The difference from step S1 of Example 1 is that 3 mL of methacrylic anhydride solution (MA) is added dropwise to the solution, and the ratio of double bonds grafted on the surface of HA is 22%, expressed as 22%-HAMA. The rest is the same as step S1 of Example 1.
[0089] S2: Same as step S2 in Example 1.
[0090] S3: The difference from step S3 of Example 1 is that 28%-HAMA is replaced with 22%-HAMA to obtain a 30 mg / mL 22%-HAMA NPs PBS solution. The rest is the same as step S3 of Example 1.
[0091] The morphology of 22%-HAMA NPs was characterized by transmission electron microscopy (TEM), and the diameter of the nanoparticles was determined to be 22±4 nm by measuring the nanoparticles obtained by transmission electron microscopy.
[0092] S4: The difference from step S4 of Example 1 is that the 30 mg / mL 28%-HAMA NPs solution is replaced by a 30 mg / mL 22%-HAMA NPs solution. The rest is the same as step S4 of Example 1.
[0093] S5: Same as step S6 in Example 1.
[0094] The storage modulus G' of the hydrogel was measured to be 5443.063 Pa and the loss modulus G" was 558.43 Pa. Fig.10 shown.
[0095] S6: Same as step S7 in Example 1.
[0096] The mass swelling ratio of the nanocolloid hydrogel was calculated to be 100.05 ± 2.92%, as Fig.11 shown.
[0097] The volume swelling ratio of the nanocolloidal hydrogel was calculated to be 102.77 ± 1.09%. Fig.12 shown.
[0098] S7: Same as step S8 in Example 1.
[0099] The storage modulus and loss modulus of the nanocolloid hydrogel changed to 5075.04Pa and 758.35Pa, 4530.34Pa and 686.92Pa, and 3815.4Pa and 772.16Pa, respectively. By comparison, the mechanical properties of the nanocolloid hydrogel were stable during the 30-day test, and no obvious decrease in modulus was observed.
[0100] S8: Same as step S9 in embodiment 1.
[0101] During the 60 days of monitoring, the nanocolloidal hydrogel was gradually and completely degraded.
[0102] S9: The difference from step S10 in Example 1 is that the 30 mg / mL 28%-HAMA NPs solution is replaced with a 30 mg / mL 22%-HAMA NPs solution. The rest is the same as step S10 in Example 1.
[0103] like Figure 7 As shown, the cell viability was good and no obvious cell death was observed, indicating that the nanocolloidal hydrogel had good cell biocompatibility.
[0104] S10: Same as step S12 in embodiment 1.
[0105] Triton X-100 was used as a positive control, and the hemolysis rate was determined to be <1%.
[0106] S11: Same as step S13 in Example 1.
[0107] The friction coefficient of the nanocolloid hydrogel is calculated to be 0.00147. Fig. 9 shown.
[0108] Embodiment 4: A method for preparing a nano-colloidal hydrogel provided by an embodiment of the present invention comprises the following steps:
[0109] S1: The difference from step S1 of Example 1 is that 5 mL of methacrylic anhydride solution (MA) is added dropwise to the solution, and the ratio of double bonds grafted on the surface of HA is 35%, expressed as 35%-HAMA. The rest is the same as step S1 of Example 1.
[0110] S2: Same as step S2 in Example 1.
[0111] S3: The difference from step S3 of Example 1 is that 28%-HAMA is replaced with 35%-HAMA to obtain a 30 mg / mL 35%-HAMA NPs PBS solution. The rest is the same as step S3 of Example 1.
[0112] The morphology of 35%-HAMA NPs was characterized by transmission electron microscopy (TEM), and the diameter of the nanoparticles was determined to be 34±10 nm by measuring the nanoparticles obtained by transmission electron microscopy.
[0113] S4: The difference from step S4 of Example 1 is that the 30 mg / mL 28%-HAMA NPs solution is replaced by a 30 mg / mL 35%-HAMA NPs solution. The rest is the same as step S4 of Example 1.
[0114] S5: Same as step S6 in Example 1.
[0115] The storage modulus G' and loss modulus G" of the hydrogel were measured to be 7950.11 Pa and 1553.36 Pa respectively.
[0116] S6: Same as step S7 in Example 1.
[0117] The mass swelling ratio of the nanocolloidal hydrogel was calculated to be 101.48±1.37%.
[0118] The volume swelling ratio of the nanocolloidal hydrogel was calculated to be 101.71±1.72%.
[0119] S7: Same as step S8 in Example 1.
[0120] The storage modulus and loss modulus of the nanocolloidal hydrogel changed to 7674.66Pa and 1104.26Pa, 7219.86Pa and 448.68Pa, and 6034.81Pa and 1185.53Pa, respectively. By comparison, the mechanical properties of the nanocolloidal hydrogel were stable during the 30-day test, and no obvious decrease in modulus was observed.
[0121] S8: Same as step S9 in embodiment 1.
[0122] No significant degradation was observed during the 180 days of monitoring.
[0123] S9: The difference from step S10 in Example 1 is that the 30 mg / mL 28%-HAMA NPs solution is replaced with a 32 mg / mL 35%-HAMA NPs solution. The rest is the same as step S10 in Example 1.
[0124] like Figure 7 As shown, the cell viability was good and no obvious cell death was observed, indicating that the nanocolloidal hydrogel had good cell biocompatibility.
[0125] S10: Same as step S12 in embodiment 1.
[0126] Triton X-100 was used as a positive control, and the hemolysis rate was determined to be <1%.
[0127] S11: Same as step S13 in Example 1.
[0128] The friction coefficient of the nanocolloid hydrogel is calculated to be 0.00157. Fig. 9 shown.
[0129] In the embodiment of the present invention, the highest concentration range of nanoparticles can reach 160 mg / mL, while the lowest concentration of 35% HAMANPs for preparing nanocolloid hydrogel is only 2 mg / mL.
[0130] Embodiment 5: A method for preparing a nano-colloidal hydrogel provided by an embodiment of the present invention comprises the following steps:
[0131] S1: Add 1g sodium hyaluronate powder (HA, Mw = 150-250KDa) to 100mL deionized water and fully dissolve it. Transfer the solution to an ice water bath at 0-4°C, add 4mL of methacrylic anhydride solution (MA) to the solution, adjust the pH of the solution to 8-9 with 5M sodium hydroxide solution, and react at 0-4°C for 24h to obtain a methacrylylated hyaluronic acid (HAMA) solution. The obtained HAMA solution is reverse precipitated in ethanol, centrifuged, the supernatant is discarded, and the precipitate is redissolved in deionized water. After dialysis for 72h, it is freeze-dried to obtain 0.8g HAMA powder. Weigh the freeze-dried powder and dissolve it in a deuterated water solvent to a concentration of 5mg / mL. The double bonds grafted on the HA surface are quantified by a nuclear magnetic resonance spectrometer. The proportion of double bonds grafted on the HA surface is 28%, expressed as 28%-HAMA.
[0132] S2: 80 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) was dissolved in 2 mL of deionized water to prepare an EDC solution; 40 mg of adipic acid dihydrazide (ADH) was dissolved in 2 mL of deionized water to prepare an ADH solution.
[0133] S3: Weigh 0.2g of 28%-HAMA powder and dissolve it in 80mL deionized water. After fully dissolved, add 132mL acetone and stir it thoroughly at room temperature for 30min. Add EDC solution and ADH solution dropwise to the 28%-HAMA solution. After fully stirring for 30min, add 130mL acetone to the solution again. After cross-linking for 3-5h, obtain 28%-HAMA nanoparticle (28%-HAMANPs) solution. The obtained 28%-HAMA NPs solution is fully dialyzed in water and concentrated by rotary evaporation. Take 200μL of concentrated 28%-HAMA NPs solution, dry it in a vacuum oven at 60℃, determine the concentration of the concentrate, dilute the concentrate with PBS solutions of different concentrations, and obtain 5mg / mL 28%-HAMA NPs PBS solution.
[0134] The morphology of 28%-HAMA NPs was characterized by transmission electron microscopy (TEM), and the diameter of the nanoparticles was determined to be 20±5 nm by measuring the nanoparticles obtained by transmission electron microscopy.
[0135] S4: Prepare a 0.3 w / v% aqueous solution of photoinitiator Irgacure 2959. Blend 500 μL of 5 mg / mL 28%-HAMA NPs solution with 100 μL of 0.3 w / v% photoinitiator solution to prepare a hydrogel precursor solution. Spread the precursor solution on a 2 cm diameter polytetrafluoroethylene mold and irradiate with a 365 nm UV light source at 10 mW / cm 2The precursor solution was photo-crosslinked to prepare nano-colloidal hydrogel by irradiation with light intensity of 120s.
[0136] S5: The prepared nanocolloidal hydrogel was carefully transferred to the rheometer platform, and a strain test experiment was performed at 25°C, 0.1% to 100% strain amplitude, and 0.1 Hz constant frequency.
[0137] The storage modulus G' and loss modulus G" of the hydrogel were measured to be 13.78 Pa and 2.16 Pa, respectively.
[0138] Embodiment 6: A method for preparing a nano-colloidal hydrogel provided by an embodiment of the present invention comprises the following steps:
[0139] S1-S3: Same as steps S1-S3 of Example 5.
[0140] S4: The difference from step S4 of Example 5 is that the 5 mg / mL 28%-HAMA NPs solution is replaced with a 100 mg / mL 28%-HAMA NPs solution. The rest is the same as step S4 of Example 5.
[0141] S5: Same as step S5 of embodiment 5.
[0142] The storage modulus G' and loss modulus G" of the hydrogel were measured to be 9358.23 Pa and 839.68 Pa respectively.
[0143] S6: Monitoring the swelling behavior of nanocolloidal hydrogels.
[0144] Volume swelling: The volume swelling ratio of the nanocolloidal hydrogel was calculated to be 102.43±1.34%.
[0145] Embodiment 7: A method for preparing a nano-colloidal hydrogel provided by an embodiment of the present invention comprises the following steps:
[0146] S1-S3: Same as steps S1-S3 of Example 5.
[0147] S4: The difference from step S4 of Example 5 is that the 5 mg / mL 28%-HAMA NPs solution is replaced with a 160 mg / mL 28%-HAMA NPs solution. The rest is the same as step S4 of Example 5.
[0148] S5: Same as step S5 of embodiment 5.
[0149] The storage modulus G' and loss modulus G" of the hydrogel were measured to be 11128.07 Pa and 1145.93 Pa respectively.
[0150] S6: Monitoring the swelling behavior of nanocolloidal hydrogels.
[0151] Volume swelling: The volume swelling ratio of the nanocolloidal hydrogel was calculated to be 101.56±1.90%.
[0152] Embodiment 8: A method for preparing a nano-colloidal hydrogel provided by an embodiment of the present invention comprises the following steps:
[0153] S1: The difference from step S1 in Example 5 is that sodium hyaluronate powder (HA, Mw=150-250KDa) is replaced with sodium hyaluronate powder (HA, Mw=3500Da), and the rest is the same as step S1 in Example 5.
[0154] S2-S3: Same as steps S2-S3 of Example 5.
[0155] S4: The difference from step S4 of Example 5 is that the 5 mg / mL 28%-HAMA NPs solution is replaced with a 30 mg / mL 28%-HAMA NPs solution. The rest is the same as step S4 of Example 5.
[0156] Embodiment 9: A method for preparing a nano-colloidal hydrogel provided by an embodiment of the present invention comprises the following steps:
[0157] S1: The difference from step S1 of Example 5 is that the sodium hyaluronate powder (HA, Mw=150-250 KDa) is replaced with sodium hyaluronate powder (HA, Mw=400 KDa), and the rest is the same as step S1 of Example 5.
[0158] S2: 80 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) was dissolved in 2 mL of deionized water to prepare an EDC solution; 40 mg of adipic acid dihydrazide (ADH) was dissolved in 2 mL of deionized water to prepare an ADH solution.
[0159] S3: The difference from step S3 of Example 5 is that a 30 mg / mL 28%-HAMA NPs PBS solution is obtained, and the rest is the same as step S3 of Example 5.
[0160] The morphology of 28%-HAMA NPs was characterized by transmission electron microscopy (TEM), and the diameter of the nanoparticles was determined to be 60±10 nm by measuring the nanoparticles obtained by transmission electron microscopy.
[0161] S4: The difference from step S4 of Example 5 is that the 5 mg / mL 28%-HAMA NPs solution is replaced with a 30 mg / mL 28%-HAMA NPs solution. The rest is the same as step S4 of Example 5.
[0162] Embodiment 10: A method for preparing a nano-colloidal hydrogel provided by an embodiment of the present invention comprises the following steps:
[0163] S1: Same as step S1 in Example 5.
[0164] S2: Dissolve 40 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) in 2 mL of deionized water to prepare an EDC solution; dissolve 20 mg of adipic acid dihydrazide (ADH) in 2 mL of deionized water to prepare an ADH solution.
[0165] S3: The difference from step S3 of Example 5 is that a 30 mg / mL 28%-HAMA NPs PBS solution is obtained, and the rest is the same as step S3 of Example 5.
[0166] The morphology of 28%-HAMA NPs was characterized by transmission electron microscopy (TEM), and the diameter of the nanoparticles was determined to be 60±10 nm by measuring the nanoparticles obtained by transmission electron microscopy.
[0167] S4: The difference from step S4 of Example 5 is that the 5 mg / mL 28%-HAMA NPs solution is replaced with a 30 mg / mL 28%-HAMA NPs solution. The rest is the same as step S4 of Example 5.
[0168] Embodiment 11: A method for preparing a nano-colloidal hydrogel provided by an embodiment of the present invention comprises the following steps:
[0169] S1: Same as step S1 in Example 5.
[0170] S2: 8 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) was dissolved in 2 mL of deionized water to prepare an EDC solution; 4 mg of adipic acid dihydrazide (ADH) was dissolved in 2 mL of deionized water to prepare an ADH solution.
[0171] S3: The difference from step S3 of Example 5 is that a 30 mg / mL 28%-HAMA NPs PBS solution is obtained, and the rest is the same as step S3 of Example 5.
[0172] The morphology of 28%-HAMA NPs was characterized by transmission electron microscopy (TEM), and the diameter of the nanoparticles was determined to be 300±20 nm by measuring the nanoparticles obtained by transmission electron microscopy.
[0173] S4: The difference from step S4 of Example 5 is that the 5 mg / mL 28%-HAMA NPs solution is replaced with a 30 mg / mL 28%-HAMA NPs solution. The rest is the same as step S4 of Example 5.
[0174] Example 12: A method for preparing a nano-colloidal hydrogel provided by an embodiment of the present invention comprises the following steps:
[0175] S1: Same as step S2 of Example 5.
[0176] S2: Weigh 0.2g sodium hyaluronate (HA, Mw = 150-250KDa) powder and dissolve it in 80mL deionized water. After fully dissolved, add 132mL acetone and stir thoroughly at room temperature for 30min. Add EDC solution and ADH solution dropwise to the HA solution, stir thoroughly for 30min, add 130mL acetone to the solution again, and crosslink for 3-5h to obtain HA NPs solution. The obtained HA NPs solution is fully dialyzed in water and concentrated by rotary evaporation. Take 200μL of concentrated HA NPs solution, dry it in a vacuum oven at 60℃, and determine the concentration of the concentrate.
[0177] S3: The HA nanoparticle solution obtained in S2 was placed in a 0-4°C ice water bath and stirred. After the temperature stabilized, 1 mL of MA solution was added dropwise to the solution, and the pH of the solution was adjusted to 8-9 with 5M NaOH. After fully reacting for 24 hours, a HAMA NPs solution was obtained. The HAMA NPs solution was dialyzed for 72 hours for further purification. After 72 hours, the nanoparticle solution was concentrated by rotary evaporation to obtain a 30 mg / mL HAMA NPs solution.
[0178] S4: Take 1mL HAMA NPs solution, add 200-400unit / mL hyaluronidase, put it in a 37℃ constant temperature water bath, add hyaluronidase once every 48 hours, freeze-dry after five days, weigh the freeze-dried powder and dissolve it in deuterated water solvent to reach a concentration of 5mg / mL, and quantify the double bonds grafted on the surface of HA nanoparticles by nuclear magnetic resonance spectrometer. The proportion of double bonds grafted on the surface of HA nanoparticles is 15%.
[0179] S5: The difference from step S4 in Example 5 is that the 5 mg / mL 28%-HAMA NPs solution is replaced with a 30 mg / mL 15%-HAMA NPs solution. The rest is the same as step S4 in Example 5.
[0180] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.
Claims
1. A method for preparing a nano-colloidal hydrogel, characterized in that: The following steps are involved: Step S1, preparation of methacrylylated hyaluronic acid nanoparticles: after sodium hyaluronate is fully dissolved in deionized water, methacrylic anhydride is added dropwise to the solution in a certain proportion under ice-water bath conditions to fully react, and a certain proportion of carbon-carbon double bonds are grafted on the surface of sodium hyaluronate to obtain a methacrylylated hyaluronic acid solution; the methacrylylated hyaluronic acid solution after the reaction is dialyzed and freeze-dried, and then redissolved in deionized water, and the carboxyl groups on the polymer chains are activated with 1-ethyl-(3-dimethylaminopropyl)carbodiimide, and acetone is added to the solution to desolvate the polymer, and then a cross-linking agent is added to cross-link the polymer chains to obtain a nanoparticle solution with a certain size, and the solution is dialyzed again and concentrated to obtain a methacrylylated hyaluronic acid nanoparticle solution; Step S2, preparation of nanocolloid hydrogel: redispersing the methacrylylated hyaluronic acid nanoparticle solution obtained in step S1 in a phosphate buffer solution containing 0.05 w / v% of a photoinitiator to prepare hydrogel precursor solutions with different concentrations; Then, a certain volume of the precursor solution is placed into a polytetrafluoroethylene mold, and then irradiated with an ultraviolet light source to prepare a nanocolloidal hydrogel; In the step S1, the cross-linking agent is adipic acid dihydrazide, spermidine or spermine.
2. The method for preparing the nano-colloidal hydrogel according to claim 1, characterized in that: In the step S2, the photoinitiator is Irgacure 2959 or 2,4,6-trimethylbenzophenone or phenyl (2,4,6-trimethylbenzoyl) lithium phosphate.
3. The method for preparing the nano-colloidal hydrogel according to claim 1, characterized in that: In step S2, the wavelength of the ultraviolet light source is 365 nm.
4. A nanocolloidal hydrogel prepared according to the preparation method according to any one of claims 1 to 3.
Citation Information
Patent Citations
Hyaluronic acid hydrogel and preparation method and application thereof
CN111592618A
Preparation method and application of supramolecule-macromolecule composite hydrogel material
CN115678047A